Avaliação da eficácia de um marcador para capsulorrexe anterior - Faria, M. A. R. (2016)
To evaluate the effectiveness of a surgical devicethat intented to help in the preparation of the anterior capsulorhexis analyzing the design and shape, comparing with capsulorhexis made by free hand.Methods:Three third-year ophthalmology residents at the Hospital Universitário Onofre Lopes and onesurgeon in training, participate in this research as volunteers. Each surgeon perform 5 capsulorhexis in porcine eyes using the device, and five others by free hand as a control. All capsulorhexis were photographed having a ruler as reference to guide and calibrate a computer application formorphometric evaluation (Cambuí Labs, Natal, Brazil). All surgeons aimed to produce a circular continuous capsulorhexis of 5 mm diameterthat represents 15,7mm in perimeter and 19,652mm2in area.Each wet-lab capsulorhexis was evaluated in regard to these criteria: diameter (mean, maximum and minimum), perimeter, area, deviation from the ideal diameter and ideal shape.Results:Compare to control groups, capsulorhexis with the aid of the surgical device by the residents and surgeon in training showed significant improvement in these evaluated criteria: 5,44mm ±0,89 (with device) vs 6,37mm ±0,67 (free hand) for capsulorhexis diameter (p=0,001); 17,52mm±1,92 (with device) vs 20,14mm ±2,09 (free hand) for capsulorhexis perimeter (<0.001); 24,73mm2±1,92 (with device) vs 32,62mm2±6,36 (free hand) for capsulorhexis area (p<0,001). A tendency for better result with the aid of the surgical device was observed for deviation of an ideal diameter or ideal aspect were appreciated: 0,87mm ±0,05 (with device) vs 0,9 ±0,04 (free hand) for deviation of a curve (p=0,06); 1,26mm ±0,12 (with device) vs 1,21mm ±0,7 (free hand) for the capsulorhexis aspect (p=0,09).Conclusion:Capsulorhexis produced with the aid of the surgical device, by surgeons in training, significantly improved wet-lab capsulorhexis performance and their measurements were close to the desired target goals.